Pengajaran Akidah dalam KalanganMualaf di Institut Dakwah Islamiyah PERKIM: Teaching of Islamic Faith (Akidah) among New Converted Muslim in Islamic Propagation Institute (PERKIM) - Kasim, Ahmad Yunus; Hamid, Samsuddin Abdul; Jemali, Misnan (Perspektif Jurnal Sains Sosial dan Kemanusiaan, 2017)
Faith education is the most important aspect of identity construction or conversion of Muslim converts as strong. The weakness of faith lead to life converts tatters confused in difficult practice of Islam and tend to go back to previous religion. Hence, this study aimed to explore the implementation of teaching the faith and pedagogicalcontent knowledge implemented during the process of teaching the faith to new Muslim converts in PERKIM. This study used quantitative and qualitative research design and case study data obtained viaquestionnaires, interviews and analysis protocol document. The process of thinking and behaviour of the lecturer in the classroom studied by circular models of pedagogy and teaching practice (Shulman, 1987). This process includes several phases, the level of understanding teaching, transformation, action learning, evaluation, and reflection in teaching. The formation of new understandings related content knowledge, pedagogical knowledge or knowledge of the subject students have contributed to the formation systematically in teaching the faith to Muslim converts. The study found PCK skill shown by all lecturers reflect the experience of 'wisdom of practice' and 'wise practice' belief in teaching the subject. The findings of this study can serve as a guide specialized in teaching the faith to the people Converts Muslim.